Representação social da epilepsia - Moreira, Antonia Silva Paredes (1991)
This work aims at surveying; social representations epilepties, their relations and non-epileptics; check the social components related to epilepsy and compared social among psico- representations, an understanding of epilepsy when it comprises the symbolic and cognitive system, thus making up the body of knowledge and its image through their experience both as epileptics and non- epileptics. Forty-five subjects were surveyed, their choice being made with criteria was according to the characteristics, from type of epilepsy, age, their acquaintance (or not) with sease and others. The information gathered were submitted this to systematic and quantitative analysis of content present in the the di- in- formation collected from the subjects interviewed. The analytical procedure was directed to five categories of representations: emotional effects, definition of epilepsy, causes of epilepsy, treat- ment and several descriptions -starting from a favorable attitu- de-positive an unfavorable one negative - and a neutral one. The main discussion of this study is based on the information collected, and we started getting interested in the problem of epi lepsy from their personal experiences in the various aspects and their expectations towards it. The subjects interviewed described epilepsy as a stigmatized disease, taking their bearers to rejection. The epileptic is represented as a victim of a disease which is bilogical and essentially social, whose attitude favored a negative direction for the representation about epilepsy and its bearers.